Problem-based Learning (PBL), Kemampuan Pemecahan Masalah, dan Self-Efficacy: A Systematic Literature Review - I Made Sudarman Utama; I Wayan Redhana; I Nyoman Tika; Ida Bagus Putu Arnyana; Ni Ketut Rapi (Jurnal Penelitian Pendidikan IPA, 2025)
Problem-solving skills and self-efficacy are essential competencies that enable students to face academic and real-life challenges, particularly in science learning. One instructional approach frequently associated with the development of these competencies is the Problem-Based Learning (PBL) model. However, research findings on the effectiveness of PBL in enhancing problem-solving skills and self-efficacy show varied results and have not been systematically synthesized, especially in the context of science education. Therefore, this study aims to identify and describe trends in research subjects, research designs, and types, as well as key findings related to the application of the PBL model to problem-solving skills and self-efficacy through a Systematic Literature Review (SLR). This study analyzed 20 research articles published over the last ten years (2016–2025) and indexed in the Directory of Open Access Journals (DOAJ). The selected articles were examined using a content analysis observation sheet to identify research subjects, methodological approaches, and key findings. The results show that research on PBL is dominated by studies conducted at the senior high school level, while research at the elementary and junior high school levels remains limited. Quantitative research designs, particularly quasi-experimental studies, predominate, with relatively few qualitative, mixed-methods, and research and development (R&D) studies. The key findings reveal variations in the achievement of problem-solving skill indicators and self-efficacy dimensions across studies. These findings indicate that although the PBL model has the potential to enhance problem-solving skills and self-efficacy, its effectiveness is influenced by student characteristics, learning contexts, and instructional design. This study highlights the need for further research, particularly at the elementary and junior high school levels, and encourages methodological diversification as well as the integration of PBL with other learning models and instructional strategies. Overall, this SLR provides a comprehensive overview that can serve as a reference for researchers and educators in developing more effective and context-sensitive PBL implementations in science education.